The Evidentiary Value of Administrative - Alwan, Ali (Journal of Legal Sciences, 2025)
This research examines the evidentiary value of administrative investigations before ordinary courts, viewing it as a connecting link between the system of institutional discipline and the system of judicial proof. The study adopts an analytical–comparative methodology: a descriptive track analyzing the legislative framework and procedural safeguards, and an applied track comparing the positions of civil and criminal courts regarding the reports of investigative committees.The findings conclude that the administrative investigation serves as a supporting presumption that does not, by itself, amount to conclusive evidence unless the guarantees of impartiality, the right of defense, reasoning, and sound documentation are fulfilled. The research further shows that establishing a disciplinary violation does not necessarily entail civil or criminal liability, due to differences in the elements and standards of proof.The study also indicates that procedural deficiencies—such as lack of reasoning or weak documentation—diminish the judicial weight of the investigation and necessitate supplementation through expert opinions and witness testimony. Moreover, it presents a practical framework to enhance the judicial admissibility of investigation outcomes through an evidence matrix and a digital chain of custody.The study recommends codifying a unified national manual for investigation procedures, adopting accreditation programs for committee members, and establishing a coordination mechanism with the public prosecution and the judiciary. These proposals aim to rationalize accountability and safeguard public funds while upholding the guarantees of a fair trial.